Comparative Analysis of Chilblain Lupus Erythematosus and Idiopathic Perniosis: Histopathologic Features and Immunohistochemistry for CD123 and CD30. (April 2018) - Wang, Michael L.; Chan, May P.
Abstract : Abstract: Distinction of chilblain lupus erythematosus (CLE) from idiopathic perniosis (IP) could predict an underlying connective tissue disease; however, histopathologic discrimination of the two is difficult. Increased CD123 + plasmacytoid dendritic cells and CD30 + lymphocytes have been demonstrated in various forms of cutaneous lupus erythematosus and IP, respectively. To our knowledge, CD123 and CD30 have not been examined in CLE. Our objective was to identify helpful histopathologic and immunohistochemical features in distinguishing CLE and IP. Skin biopsies classified as CLE (n = 20) and IP (n = 39) based on clinicopathologic correlation were collected from 2000 to 2015. Various histopathologic features were examined on hematoxylin and eosin and alcian blue stains. CD123 and CD30 immunostains were performed and characterized. We identified dermal interstitial fibrin exudate ( P = 0.0352) and increased dermal mucin ( P = 0.0002) as features significantly associated with CLE. Other histopathologic features and CD123 failed to distinguish between groups. CD30 + lymphocytes were sparse in all cases. Despite being the largest series of CLE and IP to date, the number of CLE cases in this study remained relatively limited, and some patients in the IP group may have yet to develop diagnostic features of systemic lupus erythematosus. In conclusion, histopathologic distinction between CLE and IP remains challenging. Interstitial fibrin and abundant dermal mucin help favor CLE. The number and distribution of CD123 + plasmacytoid dendritic cells and CD30 + lymphocytes have no discriminatory role.